Pengaruh Content Marketing, Electronic Word Of Mouth, Dan Persepsi Harga Terhadap Keputusan Pembelian Barang Melalui Online Shop Shopee: Studi Pada Akun Shopee 88stuffs - Putri Iyliana Natasha; Sukaris Sukaris (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
The rise of online sales encourages businesses to provide good, quality, and diverse online services. This is done to meet the expectations of consumers who are looking for ease in finding products, appropriate prices, and quality of service. In 2019, Ashoer stated that more and more businesses are trying to provide a positive online shopping experience. According to an e-commerce survey, Shopee was ranked as the top online shopper in Indonesia based on ratings in the Appstore and Playstore. Tokopedia and Lazada are also ranked highly. This research was conducted using a quantitative method, providing a description of the object under study using data or samples that have been collected as they are, without the need for thorough analysis and the creation of generalised results. The purpose of writing Investigate the extent to which the marketing content presented by 88stuffs can influence consumer views and purchasing decisions on the Shopee platform. The results involving 320 respondents show that the majority of 88stuffs consumers are women aged 15-25 years, the majority of whom come from Gresik city. Analysis of variables such as Content Marketing, Electronic Word of Mouth, Price Perception, and Purchase Decision shows that 88stuffs' business and marketing strategies are effective in influencing consumer preferences.